The Implementation Guided Inquiry Model of Teaching for 7th Grade Junior High School in Improving Cognitive Skill on Temperature Course - Erin Wardani; Zainur Rasyid Ridlo (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Science learning covers processes and products. Learning activities undertaken must follow the scientific method of observing, asking, trying, reasoning, communicating. One of the learning models that is suitable for the scientific method is the guided inquiry teaching model. This study aims to examine the implementation of the guided inquiry model of teaching in heat and temperature course in improving the cognitive learning skills of junior high school students. This type of research is a quasi-experimental research with one group pretest-posttest design research design. The sample used was one class with a total of 31 students. The pretest and posttest results were tested in pairs to determine the improvement in students' cognitive skills and the results obtained were sig. (2-tailed) is 0,000 so it is smaller than 0.05. From these results, it can be concluded that the application of the guided inquiry model of teaching in temperature and its changes can improve the cognitive skills of junior high school students.